2021
DOI: 10.1089/apc.2021.0012
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk and Pre-Exposure Prophylaxis Eligibility Among Emergency Department Patients

Abstract: Our objective was to estimate the prevalence of pre-exposure prophylaxis (PrEP) eligibility, characterize selfperceived and quantified human immunodeficiency virus (HIV) risk, and assess PrEP knowledge and receptiveness of initiating PrEP among emergency department (ED) patients. We performed an IRB-approved crosssectional study from two urban EDs. Patients were eligible if ‡18 years of age and not known to have HIV. Research staff obtained verbal consent and used a structured 29-item instrument to assess HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…This viewpoint was corroborated in our survey results, with nearly all responding clinicians in this study reporting they are comfortable with managing STI care. In addition, UC clinics serve a population similar to Emergency Departments, which prior studies have described as a prime location for PrEP implementation [ 14 - 16 ]. Yet, in a prior study, UC clinicians had many concerns, including managing side effects of PrEP, adherence to medication, and increased PrEP-associated high-risk sexual behavior [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This viewpoint was corroborated in our survey results, with nearly all responding clinicians in this study reporting they are comfortable with managing STI care. In addition, UC clinics serve a population similar to Emergency Departments, which prior studies have described as a prime location for PrEP implementation [ 14 - 16 ]. Yet, in a prior study, UC clinicians had many concerns, including managing side effects of PrEP, adherence to medication, and increased PrEP-associated high-risk sexual behavior [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ED prevention navigator actively referred patients interested in outpatient prevention services within a network of local federally qualified health centers (FQHC) identified from the East Bay Getting to Zero collaborative. 16 The ED prevention navigator assisted interested patients at higher risk for acquiring HIV by arranging outpatient linkage to HIV prevention services, working directly with navigators at partnering FQHCs. Navigators tracked the outcomes of these referrals through a combination of EHR review and telephone follow-up with patients and the outpatient clinics.…”
Section: Methodsmentioning
confidence: 99%
“…The risk survey has been previously described and included questions adapted from the 2017 CDC guidelines for PrEP, as well as 2 site-specific risk factors, sex while using stimulants in the past 6 months and requesting PrEP after meeting with the prevention navigator in the absence of other reported risk behaviors. 15,17 Patients reporting ≥1 risk behavior elicited in the survey were categorized at higher risk for acquiring HIV, all others were categorized at lower risk for acquiring HIV (see Table, Supplemental Digital Content, http://links.lww.com/QAI/C264).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the Latino SMM reported substantial social and structural barriers to PrEP uptake. Some of these barriers, including low perceived PrEP eligibility [36][37][38][39], intersectional stigma [40][41][42] (HIV, gay, and PrEP related), lack of insurance [43] or perceived cost [44], and PrEP misconceptions [45], are shared with other non-Latino groups (albeit with added complexities). Other barriers were more specific to the lives of Latino SMM.…”
Section: Principal Findingsmentioning
confidence: 99%